A triethylamine gas sensor based on sulfur-vacancy-rich ZnIn2S4 nanoflower sensitive material and its preparation method
By preparing sulfur-rich vacant ZnIn2S4 nanoflower sensitive material assembled based on {0001} crystal surface nanosheets, the problem of insufficient detection limit and response speed of triethylamine gas in the prior art is solved, and efficient gas sensing effect is achieved, suitable for use in the existing technology. Large-scale production and has important application value.
Patent Information
- Application Number
- CN202210469510.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-28
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-04-28
AI Technical Summary
The existing two-dimensional layered metal sulfide gas sensing materials face challenges such as selectivity, gas response, response time and stability in the rapid development process, especially in the detection of triethylamine gas, the lower limit and response of sensors The speed is insufficient and it is difficult to meet the safety needs of production and life.
By preparing sulfur-rich vacancies ZnIn2S4 nanoflower sensitive material assembled based on {0001} crystal surface nanosheets, using the electronic structure of sulfur-vacancies to adjust the material, combined with screen printing technology and solvent-thermal method, high-energy {0001} surface exposed nanometers were prepared by using the electronic structure of sulfur-vacancies. The sheet assembly structure forms an efficient gas sensor.
It realizes efficient detection of triethylamine gas, has fast response speed, is suitable for mass production, and has important application value. It also optimizes the gas adsorption characteristics of the material by changing the synthesis conditions, significantly improving the sensing performance.
Smart Images

Figure CN114858869B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of gas sensors, and in particular relates to a triethylamine gas sensor based on a sulfur-vacancy-rich ZnIn2S4 nanoflower sensitive material assembled from {0001} crystal plane nanosheets and a preparation method thereof. Background Art
[0002] With the rapid development of industry and technology, while material wealth is greatly enriched, production safety and environmental issues are becoming increasingly prominent. People have more and more opportunities to come into contact with dangerous gases, such as natural gas with methane and carbon monoxide as the main components, organic volatile toxic gases such as formaldehyde, benzene, and xylene released from decoration materials, and sulfur dioxide and nitrogen oxides in coal combustion and automobile exhaust. Once these flammable, explosive, toxic and harmful gases are produced or leaked, they will pose a threat to people's health and life. Therefore, it is very necessary to develop gas sensors with high responsiveness and fast detection speed.
[0003] Triethylamine is a colorless transparent liquid with a strong pungent odor. As a solvent and reactant, it is widely used in chemical fields such as antiseptic and dye. In addition, there are also a large number of reports confirming that the bodies of fish and other marine organisms after death will emit triethylamine gas during the process of corruption. However, incorrect contact with triethylamine gas can cause irreversible damage to human liver, kidney, lung, etc. Therefore, the development of a sensor with a low detection limit and fast response speed for triethylamine is crucial for people's production and life.
[0004] The basic principle of two-dimensional (2D) layered metal sulfide gas sensing is mainly based on the charge transfer process between gas molecules and the surface of the sensing material. Unlike traditional metal oxides, 2D materials act as charge acceptors or donors, resulting in a change in the resistance (or conductance) of the entire system. Once exposed to reactive gases, gas molecules are adsorbed on the surface of the 2D material by electrostatic forces. The direction of the electron charge transfer depends on the type of reactive gas (reducing or oxidizing). As the gas molecules desorb when exposed to air, the resistance of the sensing material returns to its initial value. The amount of resistance modulation is determined by the charge affinity of the electrons released or absorbed by the reactive gas. 2D layered metal sulfide materials show the advantages of multiple chemical properties and tunable band gaps, making them more beneficial in the design of practical gas sensing devices.
[0005] However, in the rapidly developing gas sensing applications of two-dimensional layered metal sulfide materials, challenges such as selectivity, gas response, response time, recovery time and stability still need to be addressed. To address this issue, layer-related properties and surface structure modifications, such as exposure of specific edge sites, chemical doping and ligand conjugation, have been studied to improve the sensing performance of the materials. Due to the mutual influence between the crystal plane and gas sensing, nanosheet materials can be thinned to a few nanometers and shaped to expose a unique high-energy surface, allowing them to fully utilize size and surface effects in the gas sensing process. In addition, in practical applications, the appearance of vacancy defects helps to regulate gas adsorption characteristics and material properties. The existence of these properties confirms that the introduction of sulfur (S) vacancies in ultrathin two-dimensional semiconductor lattices is an effective strategy to adjust the electronic structure of materials and achieve high-performance sensing.
[0006] ZnIn2S4 is an ultra-thin two-dimensional material with a S-Zn-S-In-S-In-S type stacked structure, and its surface activity depends largely on the main {0 0 0 1} crystal plane. At the same time, affected by the formation energy of each defect in the ZnIn2S4 micro / nano crystal, it is easier to form lattice sulfur vacancy defects. Therefore, in combination with these characteristics, the present invention synthesizes ZnIn2S4 crystals with {0 0 01} crystal plane exposure, and controls the content of S in the material lattice by changing the synthesis conditions, thereby optimizing the gas adsorption characteristics in the ZnIn2S4 micro / nano crystals, and showing efficient gas sensing performance. Summary of the invention
[0007] The purpose of the present invention is to provide a triethylamine gas sensor based on a sulfur vacancy-rich ZnIn2S4 nanoflower sensitive material assembled by {0001} crystal plane nanosheets and a preparation method thereof. The method of the present invention is simple and easy to implement, has few steps, low cost, and low equipment requirements, can improve the gas sensitive response of the gas sensor to triethylamine, is suitable for mass production, and has important application value.
[0008] The triethylamine gas sensor based on the sulfur vacancy-rich ZnIn2S4 nanoflower sensitive material assembled by {0001} crystal plane nanosheets of the present invention is composed of an Al2O3 substrate, a Pd metal interdigital electrode and a sulfur vacancy-rich ZnIn2S4 nano-sensitive material layer based on {0001} crystal plane nanosheets assembled and coated on the Pd metal interdigital electrode from bottom to top, and the nanomaterial sensitive layer is prepared by the following method:
[0009] Under room temperature, a metal precursor consisting of 0.28~0.30g zinc nitrate hexahydrate and 0.43~0.45g anhydrous indium chloride with a fixed stoichiometric ratio of 1:2 was dissolved in 55~60mL deionized water, and then 0.30~0.60g thioacetamide, 0.03g~0.09g citric acid and 0.01~0.02g polyethylene glycol (PEG, 2000~4000MW) were added and stirred vigorously for 10~20min; the obtained mixed solution was transferred to a reactor and reacted at 150~170℃ for 11~13h. After cooling to room temperature, the product was centrifuged and washed with ethanol, and the centrifuged product was dried at 60~80℃ for 24~30h to obtain a sulfur-vacancy-rich ZnIn2S4 nanoflower sensitive material based on {0001} crystal plane nanosheet assembly.
[0010] The method for preparing a triethylamine gas sensor based on a sulfur vacancy-rich ZnIn2S4 nanoflower sensitive material assembled by {0001} crystal plane nanosheets of the present invention comprises the following steps:
[0011] 1) Treatment of Pd metal interdigitated electrodes:
[0012] The Al2O3 substrate with Pd metal interdigital electrodes was wiped clean with acetone and ethanol cotton balls respectively, and then the Al2O3 substrate with Pd metal interdigital electrodes was placed in acetone, ethanol and deionized water in turn, and ultrasonically cleaned for 5-10 minutes respectively, and finally dried at 100-120°C;
[0013] The present invention uses screen printing technology to prepare Pd metal interdigital electrodes on an Al2O3 substrate. The specific method is as follows: ink [Jiahua JX07500487], Pd powder and a diluent are mixed in a mass ratio of 1:1:2, and stirred to form a paste; then the paste is injected onto a screen plate with an interdigital electrode pattern, the paste is scraped at an inclination angle of 30° to 45° and a pressure of 5 to 10 Newtons, the interdigital electrodes are printed on the Al2O3 substrate and dried, and the preparation of the Pd metal interdigital electrodes is completed after ultraviolet light curing. The width and electrode spacing of the Pd metal interdigital electrodes are both 0.15 to 0.20 mm, the thickness is 100 to 150 nm, and the number of pairs of interdigital electrodes is 5 to 10 pairs.
[0014] 2) Preparation of triethylamine gas sensor based on sulfur-vacancy-rich ZnIn2S4 nanoflower sensitive material assembled by {0001} crystal plane nanosheets:
[0015] The sulfur-vacancy-rich ZnIn2S4 nanoflower sensitive material assembled based on {0001} crystal plane nanosheets was placed in a mortar and ground for 20 to 30 minutes to obtain nanomaterial powder; deionized water was then dripped into the mortar and ground for another 20 to 30 minutes to obtain a viscous slurry; the mass ratio of the nanomaterial to deionized water was 5:1 to 3; a small amount of the slurry was applied with a small brush and coated on an Al2O3 substrate with Pd metal interdigital electrodes to completely cover the Pd metal interdigital electrodes. Finger electrode and Al2O3 substrate, which are then dried at 60~80°C to obtain a ZnIn2S4 nanoflower sensitive material sensitive layer with a thickness of 2~4μm; finally, aged for 48~72 hours under a direct current of 60~80mA in an environment with a relative humidity of 20%~40%RH and a temperature of 20~35°C, thereby obtaining a gas sensor based on sulfur vacancy-rich ZnIn2S4 nanoflower sensitive material assembled by {0001} crystal plane nanosheets.
[0016] The invention uses a CGS-1TP gas-sensing performance tester produced by Beijing Elite Technology Co., Ltd. to test the gas-sensing performance of triethylamine.
[0017] Compared with the prior art, the present invention has the following advantages and positive effects:
[0018] In the present invention, sulfur-vacancy-rich ZnIn2S4 nanoflower sensitive materials based on {0001} crystal plane nanosheet assembly are synthesized by changing the synthesis conditions. The ZnIn2S4 nanoflower sensitive materials grown by S defect engineering control are self-assembled by nanosheets exposing high-energy {0001} planes, and have a large number of S vacancies on the surface that can be used as sensing reaction active sites, so they have good detection performance for triethylamine gas. At the same time, the process adopted by the present invention is simple, the device obtained is small in size, and is suitable for mass production, so it has important application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0020] Figure 1The XRD characteristic curves of the sulfur-rich vacancy ZnIn2S4 nanoflower sensitive material (S1-S3) assembled based on {0001} crystal plane nanosheets correspond to the standard pattern of hexagonal ZnIn2S4 (JCPDS NO.65-2023). In addition, no characteristic peaks of binary metal sulfides, oxides and other organic compounds appear, indicating that the synthesized samples have good purity.
[0021] Figure 2 The SEM characterization images of sulfur-vacancy-rich ZnIn2S4 nanoflower sensitive materials assembled based on {0001} crystal plane nanosheets (Figures a~c correspond to sensitive materials S1-S3 respectively) show that these ZnIn2S4 materials all present similar morphologies of nanoflower sensitive materials, among which the diameter of the nanoflower sensitive material is 4~8μm.
[0022] Figure 3 a-3b is the TEM morphology of the sulfur-rich vacancy ZnIn2S4 nanoflower sensitive material (S2) assembled based on {0001} crystal plane nanosheets. Figure 3 c-3d are HRTEM morphology images of nanoflower sensitive material (S2). Figure 3 a and Figure 3 b It can be seen that the ZnIn2S4 nanoflower sensitive material is self-assembled from ultra-thin nanosheets. Figure 3 c Many discontinuous lattice fringes were observed, which were lattice defects formed on the surface of these nanosheets by the combined action of solvothermal method and excess thioacetamide. Figure 3 d It is found that the lattice spacing of S2 is 0.33nm, which corresponds to the {0001} plane of hexagonal ZnIn2S4.
[0023] Figure 4 The XPS total spectrum of sulfur-rich vacancy ZnIn2S4 nanoflower sensitive materials (S1-S3) assembled based on {0001} crystal plane nanosheets. It can be observed that by changing the synthesis conditions, the intensity and size of the peaks of Zn 2p and In 3d in the ZnIn2S4 sample began to decrease. This phenomenon indicates that the loss of S atoms around Zn and In promotes the formation of sulfur defects.
[0024] Figure 5 This is a schematic structural diagram of the triethylamine gas sensor based on the sulfur vacancy-rich ZnIn2S4 nanoflower sensitive material assembled based on {0001} crystal plane nanosheets prepared in the present invention; from bottom to top, it consists of an Al2O3 substrate 1, a Pd metal interdigital electrode 3, and a ZnIn2S4 nanosensitive material layer 2 coated on the Pd metal interdigital electrode and the Al2O3 substrate.
[0025] Figure 6The response curves of the devices S1, S2 and S3 prepared in the present invention at different operating temperatures under a triethylamine gas concentration of 100 ppm; Figure 6 As shown, when the device S2 is operated at a temperature of 90°C and a triethylamine concentration of 100 ppm, the maximum value of the responsivity is 1013. It can be seen that the optimal operating temperature of the device S2 is 90°C.
[0026] Figure 7 The schematic diagram is a schematic diagram of the selective characteristics of the device S1, device S2 and device S3 prepared by the present invention for the gas to be tested with a concentration of 100 ppm at an operating temperature of 90°C. Figure 7 As shown, under the conditions of operating temperature of 90°C and gas concentration of 100 ppm, device S2 exhibits good selectivity for triethylamine.
[0027] Figure 8 The response-triethylamine concentration characteristic curves of the device S1, device S2 and device S3 prepared by the present invention at an operating temperature of 90°C; the response of the gas sensor (R a / R g ) is defined as the resistance R between the sensor interdigital electrodes in air a and the resistance R in triethylamine g It can be found from the figure that at an operating temperature of 90°C, the responsiveness of device S2 increases with the increase of triethylamine concentration, and the curve shows a good linear relationship in the triethylamine concentration range of 1~100ppm. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work, any modifications, equivalent substitutions, improvements, etc., should be included in the protection scope of the present invention.
[0029] Embodiment 1:
[0030] 1. Treatment of Pd metal interdigital electrodes:
[0031] The Al2O3 substrate with Pd metal interdigital electrodes was wiped clean with acetone and ethanol cotton balls respectively, and then the Al2O3 substrate with Pd metal interdigital electrodes was placed in acetone, ethanol and deionized water in turn, and ultrasonically cleaned for 5 minutes respectively, and finally dried at 100°C;
[0032] The present invention uses screen printing technology to prepare Pd metal interdigital electrodes on an Al2O3 substrate. The specific method is as follows: ink [Jiahua JX07500487], Pd powder, and a diluent are mixed in a mass ratio of 1:1:2, and stirred to form a paste; then the paste is injected onto a screen plate with an interdigital electrode pattern, the paste is scraped at an inclined angle of 30° and a pressure of 5 Newtons, the interdigital electrodes are printed on the Al2O3 substrate and dried, and the preparation of the Pd metal interdigital electrodes is completed after ultraviolet light curing. The width and electrode spacing of the Pd metal interdigital electrodes are both 0.15 mm, the thickness is 150 nm, and the number of pairs of interdigital electrodes is 5 pairs.
[0033] 2. Preparation of sulfur-rich vacancy ZnIn2S4 nanoflower sensitive materials based on {0001} crystal plane nanosheet assembly:
[0034] At room temperature, a metal precursor consisting of 0.29g of zinc nitrate hexahydrate and 0.44g of anhydrous indium chloride with a fixed stoichiometric ratio of 1:2 was dissolved in 60mL of deionized water. Then, 0.30 of thioacetamide, 0.03g of citric acid and 0.02g of polyethylene glycol (PEG, 2000MW) were added to the solution and stirred vigorously for 20min. The above solution was transferred to a reactor and reacted at 160°C for 12h; after cooling to room temperature, the product was centrifuged and washed with ethanol, and the centrifuged product was dried at 60°C for 24 hours to obtain a sulfur-rich vacancy ZnIn2S4 nanoflower sensitive material based on {0001} crystal plane nanosheet assembly, and the product mass was 0.40g.
[0035] 3. Preparation of gas sensor:
[0036] Preparation of gas sensor based on sulfur-rich vacancy ZnIn2S4 nanoflower sensitive material assembled from {0001} crystal plane nanosheets: put the obtained sulfur-rich vacancy ZnIn2S4 nanoflower sensitive material assembled from {0001} crystal plane nanosheets into a mortar and grind for 30 minutes to obtain a powder of the nanomaterial; the mass ratio of the nanomaterial to deionized water is 5:2; then drip deionized water into the mortar and continue grinding for 30 minutes to obtain a viscous slurry; use a small brush to pick up a small amount of the slurry and apply it on On an Al2O3 substrate with a Pd metal interdigital electrode, it is then dried at 80°C to obtain a ZnIn2S4 nano-sensitive material layer with a thickness of 2μm on the surface of the Pd metal interdigital electrode; finally, it is aged for 48 hours under a direct current of 80mA in an environment with a relative humidity of 30%RH and a temperature of 25°C, thereby obtaining a gas sensor based on sulfur-vacancy-rich ZnIn2S4 nanoflower sensitive material assembled by {0001} crystal plane nanosheets, marked as S1 (Example 1).
[0037] After the gas sensor was prepared, its triethylamine gas-sensing performance was tested (CGS-1TP gas-sensing performance tester from Beijing Elite Technology Co., Ltd.).
[0038] Example 2
[0039] The processing process of the Pd metal interdigital electrode is the same as that of Example 1.
[0040] At room temperature, a metal precursor consisting of 0.29g of zinc nitrate hexahydrate and 0.44g of anhydrous indium chloride with a fixed stoichiometric ratio of 1:2 was dissolved in 60mL of deionized water. Then, 0.45 of thioacetamide, 0.06g of citric acid and 0.02g of polyethylene glycol (PEG, 2000MW) were added to the solution and stirred vigorously for 20min. The above solution was transferred to a reactor and reacted at 160°C for 12h; after cooling to room temperature, the product was centrifuged and washed with ethanol, and the centrifuged product was dried at 60°C for 24 hours to obtain a sulfur-rich vacancy ZnIn2S4 nanoflower sensitive material based on {0001} crystal plane nanosheet assembly, with a product mass of 0.41g.
[0041] Preparation of a gas sensor based on sulfur-vacancy-rich ZnIn2S4 nanoflower sensitive material assembled from {0001} crystal plane nanosheets: The experimental process is the same as in Example 1, and the device prepared based on this material is marked as S2.
[0042] Example 3
[0043] The preparation process of the Pd metal interdigitated electrode is the same as that in Example 1.
[0044] At room temperature, a metal precursor consisting of 0.29 g of zinc nitrate hexahydrate and 0.44 g of anhydrous indium chloride with a fixed stoichiometric ratio of 1:2 was dissolved in 60 mL of deionized water. Then, 0.60 g of thioacetamide, 0.09 g of citric acid and 0.02 g of polyethylene glycol (PEG, 2000 MW) were added to the solution and stirred vigorously for 20 min. The above solution was transferred to a reactor and reacted at 160 ° C for 12 h; after cooling to room temperature, the product was centrifuged and washed with ethanol, and the centrifuged product was dried at 60 ° C for 24 hours to obtain a sulfur-rich vacancy ZnIn2S4 nanoflower sensitive material based on {0001} crystal plane nanosheet assembly, and the product mass was 0.42 g.
[0045] Preparation of a gas sensor based on sulfur-vacancy-rich ZnIn2S4 nanoflower sensitive material assembled from {0001} crystal plane nanosheets: The experimental process is the same as in Example 1, and the device prepared based on this material is marked as S3.
[0046] The gas sensing performance of the gas sensor prepared in the above embodiment, which uses sulfur-vacancy-rich ZnIn2S4 nanomaterials assembled on {0001} crystal plane nanosheets as the sensitive layer and Pd as the metal Pd metal interdigital electrode, is tested using the CGS-1TP gas sensing performance tester of Beijing Elite Technology Co., Ltd.
[0047] After the gas sensor was prepared, its triethylamine gas-sensing performance was tested.
[0048] At 90℃, the responsivity of device S1 to 100 ppm triethylamine is 646, and the response time is 5 s. At 90℃, the responsivity of device S2 to 100 ppm triethylamine is 1013, and the response time is 4 s. At 90℃, the responsivity of device S3 to 100 ppm triethylamine is 733, and the response time is 1 s.
[0049] The above-described contents are only specific implementation modes of the present invention and cannot be used to limit the scope of implementation of the present invention. Any equivalent changes and improvements made according to the scope of the patent application of the present invention should still fall within the scope covered by the patent of the present invention.
Claims
1. A triethylamine gas sensor based on a sulfur-vacancy-rich ZnIn2S4 nanoflower sensitive material assembled on a {0001} crystal plane nanosheet, which is composed of an Al2O3 substrate, a Pd metal interdigital electrode, and a sulfur-vacancy-rich ZnIn2S4 nanoflower sensitive material layer assembled on a {0001} crystal plane nanosheet coated on the Pd metal interdigital electrode from bottom to top, and the nanoflower sensitive material layer is prepared by the following method: Under room temperature conditions, a metal precursor consisting of 0.28-0.30 g zinc nitrate hexahydrate and 0.43-0.45 g anhydrous indium chloride with a fixed stoichiometric ratio of 1:2 was dissolved in 55-60 mL deionized water, and then 0.30-0.60 g thioacetamide, 0.03 g-0.09 g citric acid and 0.01-0.02 g polyethylene glycol (PEG, 2000-4000 MW) were added and stirred vigorously for 10-20 min; the obtained mixed solution was transferred to a reactor and reacted at 150-170 ° C for 11-13 h. After cooling to room temperature, the product was centrifuged and washed with ethanol, and the centrifuged product was dried at 60-80 ° C for 24-30 hours, thereby obtaining a sulfur-vacancy-rich ZnIn2S4 nanoflower sensitive material based on {0001} crystal plane nanosheet assembly; wherein, The diameter of the sulfur-rich vacancy ZnIn2S4 nanoflower sensitive material assembled based on the {0001} crystal plane nanosheets is 4~8μm, and the thickness of the sulfur-rich vacancy ZnIn2S4 nanoflower sensitive material layer assembled based on the {0001} crystal plane nanosheets is 2~4μm.
2. A triethylamine gas sensor based on sulfur vacancy-rich ZnIn2S4 nanoflower sensitive material assembled by {0001} crystal plane nanosheets as claimed in claim 1, characterized in that: The width and spacing of the Pd metal interdigital electrodes are both 0.15~0.20 mm, the thickness is 100~150 nm, and the number of pairs of interdigital electrodes is 5~10 pairs.
3. A method for preparing a triethylamine gas sensor based on a sulfur vacancy-rich ZnIn2S4 nanoflower sensitive material assembled by {0001} crystal plane nanosheets according to claim 1 or 2, the steps of which are as follows: 1) Treatment of Pd metal interdigital electrodes: The Al2O3 substrate with Pd metal interdigital electrodes was wiped clean with acetone and ethanol cotton balls respectively, and then the Al2O3 substrate with Pd metal interdigital electrodes was placed in acetone, ethanol and deionized water in turn, and ultrasonically cleaned for 5-10 minutes respectively, and finally dried at 100-120°C; 2) Preparation of triethylamine gas sensor based on sulfur-vacancy-rich ZnIn2S4 nanoflower sensitive material assembled by {0001} crystal plane nanosheets: The sulfur-vacancy-rich ZnIn2S4 nanoflower sensitive material assembled based on {0001} crystal plane nanosheets is placed in a mortar and ground for 20 to 30 minutes to obtain nanomaterial powder; deionized water is then dripped into the mortar and ground for another 20 to 30 minutes to obtain a viscous slurry; a small amount of the slurry is taken with a small brush and coated on an Al2O3 substrate with Pd metal interdigital electrodes so that the slurry completely covers the Pd metal interdigital electrodes and the Al2O3 substrate, and then dried at 60 to 80°C to obtain a ZnIn2S4 nanoflower sensitive material layer with a thickness of 2 to 4 μm; finally, the gas sensor is aged for 48 to 72 hours under a direct current of 60 to 80 mA in an environment with a relative humidity of 20% to 40% RH and a temperature of 20 to 35°C, thereby obtaining a gas sensor based on the sulfur-vacancy-rich ZnIn2S4 nanoflower sensitive material assembled based on {0001} crystal plane nanosheets.
4. The method for preparing a triethylamine gas sensor based on a sulfur vacancy-rich ZnIn2S4 nanoflower sensitive material assembled by {0001} crystal plane nanosheets as claimed in claim 3, characterized in that: In step (2), the mass ratio of nanomaterial to deionized water is 5:1-3.